Les Tic: Le Rêve d’une Nouvelle Ère de L’enseignement des Langues à L’université Algérienne - Hamdad, Amele (جامعة الجزائر 2 - كلية اللغة العربية وآدابها واللغات الشرقية, 2021)
تركز مقالتنا على استخدام الموارد عبر الإنترنت من قبل معلمي ELF في الجامعة الجزائرية، عند إعداد الدورات والمواد الاختبارية. في هذا البحث، نجري دراسة استقصائية لمعلمي اللغة الفرنسية في إحدى الجامعات الجزائرية (جامعة باتنة 2) لمعرفة درجة مساهمة تقنيات المعلومات والاتصالات في ممارساتهم المختلفة. نسعى في الواقع من خلال هذا العمل إلى إظهار أن تكنولوجيا المعلومات والاتصالات حاضرة في ممارسات التدريس لغالبية معلمي الجامعات وأنهم مصدر لا يسمح لهم بإعداد دروس لغتهم وكذلك مواد الامتحانات. ومع ذلك، نعتقد أن غالبية هؤلاء المدرسين في برنامج التعلم السريع لم يستفدوا من التدريب على تكنولوجيا المعلومات والاتصالات وأن الجامعة الجزائرية لا تزودهم بأدوات الكمبيوتر التي تسهل مهمتهم التعليمية. Our article focuses on the use of online resources by FLE teachers at the Algerian University when preparing courses and test subjects. We are carrying out in this research a survey carried out with French teachers at one of the Algerian universities (Batna 2 University) to know the degree of the contribution of information and communication technologies (ICT) in their different practices of the classroom. We seek, in fact, through this work, to show that ICTs are present in the teaching practices of the majority of university teachers and that they are an inexhaustible source which allows them to prepare their language lessons as well as the subjects of exams. However, we believe that the majority of these FLE teachers have not benefited from ICT training and that the Algerian university does not provide them with the computer tools that facilitate their pedagogical task.
Keywords: تكنولوجيا المعلومات -- العملية التعليمية -- تدريس اللغات -- مؤسسات التعليم العالي -- الجزائر